Electrophysiological and behavioural responses to consonant and dissonant piano chords as standardised affective stimuli - Kirsanov, Alexander; Koriakina, Maria; Panasenko, Denis; Nikishkina, Uliana; Blagovechtchenski, Evgeny (Frontiers in Human Neuroscience, 2025)
Although the difference between consonance and dissonance has raised interest for decades in various fields of science, isolated chords are still underutilised as standardised affective stimuli in neuroscience. In the present study, we assessed whether consonant, dissonant, and neutral sounds evoked different subjective and neurophysiological responses associated with the emotional experience. For the first time, we conducted a comprehensive study of piano timbre chord perception, combining behavioural assessments, event-related potentials (ERPs), frequency-domain electroencephalography (EEG) analysis of amplitude, neurodynamic (longrange temporal correlations (LRTC)) factors, and source analysis. In an experiment, 30 participants rated the valence of sounds (consonance, dissonance, neutral) whilst simultaneously undergoing EEG recordings. At the behavioural level, a stable valence gradient was revealed: consonance was perceived as pleasant, dissonance as unpleasant, and the neutral group of stimuli as neutral. Analysis of ERPs revealed differences in response across three time windows (90–110 ms, 190–210 ms, 290–310 ms) and activation of frontotemporal and temporoparietal areas during the processing of dissonant chords. At the level of frequency and neurodynamic indices (gamma and beta bands amplitudes and LRTC), we demonstrated that classification accuracy depends on the interaction between chord type and the EEG’s amplitude- and scale-invariant characteristics for dissonant and neutral stimuli. These results provide evidence that isolated chords evoke differentiated emotional and cognitive responses, highlighting their potential utility as affective stimuli in future studies.